LIQUIDITY ANALYSIS OF PUBLIC SECTOR BANKS IN INDIA - Ravi Saini; Pooja Yadav (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
CAMEL model is used to rating the banks according to their performance. An analysis has been made by computing mean rank and overall rank of the banks under study. Here mean rank has been computed as the average of final ranks obtained by each bank on the basis of ratios under different measures of CAMEL Rating Model and then overall rank has been assigned to the banks based on their mean ranks on the rationale of assigning highest overall rank based on least meanrank.From the overall analysis, it can be concluded that State Bank of India performed best followed by PNB and BOB which also showed good performance in various measures of CAMEL Model. Central Bank of India secured overall third and last position.